Impact of reactor neutron spectrum on measured spectrum averaged cross sections. (15th December 2022) - Košťál, Michal; Losa, Evžen; Simakov, Stanislav; Schulc, Martin; Šimon, Jan; Rypar, Vojtech; Mareček, Martin; Uhlíř, Jan; Czakoj, Tomáš; Trkov, Andrej; Capote, Roberto
Highlights: Measurement of reaction rates in VR-1 reactor. Calculation of reaction rates in IRDFF-II. Effect of gamma on reaction rates of dosimetrical reaction. Discrepancies in gamma induced cross sections on gold. Abstract: The cross section averaged over 235 U thermal-neutron induced fission spectrum is a fundamental quantity that can be used in evaluation and validation of nuclear data. Many experiments focused on the determination of Spectrum Averaged Cross Sections (SACS) in 235 U(nth, f) Prompt Fission Neutron Spectrum (PFNS) in light water reactors using enriched uranium fuel. In these reactors, there is already some amount of water moderator between the uranium fuel and the irradiated sample. Due to the decrease of hydrogen cross-section with neutron energy, the high energy tail of the reactor spectrum in cores with water moderator may be harder than the pure PFNS. This paper aims to compare the shape of the actual reactor spectrum in various core positions of a research light-water reactor differing each from other by the effective water thickness. The spectrum shape is determined both by calculations and experimentally using various high energy threshold reactions. The impact of the photo-nuclear reactions (γ, n) competing with (n, 2n) in production of the same residual nucleus was shown to be less than a percent for most of studied dosimeters. An important exception was found for 197 Au(n, 2n) 196 Au dosimeter irradiated in the outcore channel where a notable photo-neutron contribution to the production of 196 Au is caused by the neutron production from the high energy γ-rays from thermal-neutron capture in 54 Fe. The corresponding ENDF/B-VIII.0 data turned out to underestimate such γ-yield by 40 % in comparison with ENDF/B-VI.8. This has improved but however not resolved the disagreement between our measurement and calculations. The remaining deficiency was attributed to the underestimation of the evaluated cross section IAEA/PD-2019 for the 197 Au(γ, n) cross section near the reaction threshold. The later was confirmed by comparison with existing measured data.